Challenges of adopting the role of care manager when implementing the collaborative care model for people with common mental illnesses: A scoping review. (27th February 2019) - Girard, Ariane; Ellefsen, Édith; Roberge, Pasquale; Carrier, Jean‐Daniel; Hudon, Catherine
Abstract: This review aimed to identify the main factors influencing the adoption of the role of care manager (CM) by nurses when implementing the collaborative care model (CCM) for common mental illnesses in primary care settings. A total of 19 studies met the inclusion criteria, reporting on 14 distinct interventions implemented between 2000 and 2017 in five countries. Two categories of factors were identified and described as follows: (i) strategies for the CCM implementation (e.g. initial care management training and supervision by a mental health specialist) and (ii) context‐specific factors (e.g. organizational factors, collaboration with team members, nurses' care management competency). Identified implementation strategies were mainly aimed towards improving the nurse's care management competency, but their efficacy in developing the set of competencies needed to fulfil a CM role was not well demonstrated. There is a need to better understand the relationship between the nurses' competencies, the care management activities, the strategies used to implement the CCM and the context‐specific factors. Strategies to optimize the adoption of the CM role should not be solely oriented towards the individual's competency in care management, but also consider other context‐specific factors. The CM also needs a favourable context in order to perform his or her activities with competency.